DETERMINAN KINERJA KEUANGAN ASURANSI SYARIAH DI INDONESIA PERIODE 2014-2016 - Audina Ayu Hidayati; Atina Shofawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
This study aims to determine the effect of exogenous variables Leverage, liquidity, Company Size, and Company Age on profitability with proxy ROA. This research uses quantitative approach by using secondary data in the form of financial statements of sharia insurance companies which listed on Otoritas Jasa Keuangan (OJK) in year 2014-2016. Regression result by using technique of panel data analysis with eviews 6. In this reasearch shows that the variables of Leverage, Liquidity, Company SizeandCompany Agesignificant effect on the profitability of sharia insurance companies simultaneously. Partially, significant Leverage and Company Age at 0,1 (10%) has significant negative effect towards on ROA but there is no effect in the variables of liquidity andCompany Sizetowards on Profitability of 93.8%. for 6,2 %, it is affected by other variables which are not included in this research.   REFERENCESAli, H. 2004. Asuransi dalam Perspektif Hukum Islam. Jakarta: Prenada Media.Almajali, A. Y. 2012. Factor Affecting the Financial Performance of Jordanian Insurance Companies Listed at Amman Stock Exchange. Journal of Management Research Vol.4, No. 2, 1941-899X.Bambang, Juanda dan Juandi. 2012. Buku Ekonometrika Deret Waktu.Brigham dan Houston. 2006. Dasar-Dasar Manajemen Keuangan. Jakarta: PT Salemba EmpatDepartemen Agama Republik Indonesia. 2008. Al-Qur’an dan Terjemahan. Semarang: CV. Toha PutraDerbali, Abdelkader. 2014. Determinants of Performance of Insurance Companies in Tunisia: The case of Life Insurance. Tunisia.Ghozali, I. 2011. Analisis Multivariate Program IBM SPSS 19. Semarang: Badan Penerbit Universitas DiponegoroGibson. 2001. Financial Reporting and Analysis: Using Financial Accounting Information, USA: South Western-Thomson Learning.Gujarati, Damodar. 2006. Dasar-Dasar Ekonometrika. Jakarta: ErlanggaHaniffa, R.M, & Cooke. 2002. Culture, Corporate Governance and Disclosure in Malaysia Coporation. AbacusHasbi, H. (2013). Sistem Peringatan Dini Sebagai Pendukung Kinerja Perusahaan Asuransi Syariah. Journal Keuangan dan Perbankan. Vol. 17, No.2, 243-252.Horne, James C. and Wachowicz, Jr, John M. 2012. Prinsip-prinsip Manajemen Keuangan. Jakarta: Salemba Empat.Janwari, Yadi. 2005. Asuransi Syariah. Bandung:Pustaka Bani QuraisyJumingan. 2011. Analisis Laporan Keuangan. Jakarta: Bumi AksaraKasmir. 2011. Pengantar Manajemen Keuangan. Jakarta: Kencana Prenada Media GroupMalik, H. (2011). Determinants Of Insurance Companies Profitability: An anlysis Of Insurance Sector Of Pakistan. Academic Research Internasional Volume IMardian, Sepky & Nurlatifah, Ai Fitri 2016. Kinerja Keuangan Perusahaan Asuransi Syariah di Indonesia: Surplus On ContributionMehari, D., & Aemiro, T. 2013. Firm apecific Factors That Determine Insurance Companies Performance In Ehtiopia. European Scientific Journal edition 9Moeljadi. 2005. Manajemen Keuangan Pendekatan Kuantitatif dan Kualitatif. Malang: Jilid 1Mysharing.co. (2015) Ekonomi Syariah akan lebih baik pada 2015. Retrieved from My Sharing Berita Ekonomi dan Keuangan Syariah.Omondi, Maleya M. & Maturi, Willy. 2013. Factors Affecting The Financial Performance of Listed Companies at the Nairobi Securities Exchange in Kenya. Research Journal of Finance and Accounting. Vol.4, No.15.Otoritas Jasa Keuangan. 2015. Statistik perasuransian Syariah tahun 2015.    Jakarta:OJKPutri, A.P. & Lestari (2014). Faktor-faktor yang Menentukan Kinerja Perusahaan Asuransi yang Terdaftar di Bursa Efek Indonesia. E-journal manajemen fakultas ekonomi, voluke I nomor 2 , 1-20.Raditya, Nurul. 2012. Analisis Faktor-Faktor yang Mempengaruhi Tingkat Pengungkapan Islamic Social Reporting (ISR) pada Perusahaan yang Masuk Daftar Efek Syariah (DES). Depok:Skripsi Fakultas Ekonomi UISartono, Agus. 2010. Manajamen Keuangan Teori dan Aplikasi. Yogyakara: BPFE.Shihab, Q.M. 2002. Tafsir Al-Mishbah. Jakarta: Lentera HatiSingapurwoko, Arif. 2011. The Impact Finacial Leverage to Profitability Study of Non-Financial Companies Listed in Indonesia Stock Exchange. European Journal of Economics, Finance and Administrative Sciences.Sugiyono. 2004.Metode Penelitian. Bandung: Sudana, I Made. 2009. Manajemen Keuangan: Teori dan Praktik. Surabaya: Airlangga University Press.Sula, Muhammad Syarkir, Prinsip-Prinsip dan Sitem Operasioanal Takaful serta Perbedaannya dengan Asuransi Konvensional, Draft Skripsi pada Asosiasi Ahli Manajemen Asuransi Indonesia (AAMAI)Wibisono. 2005. Metode Statistika. Yogyakarta: Gadjah Mada University Press.Widarjono, Agus. 2013. Ekonometrika:Pengantar dan Aplikasinya. Ekonosia, JakartaWirdyaningsih. 2005. Bank dan Asuransi Islam di Indonesia. Jakarta: Prenada Media.